2017
DOI: 10.30638/eemj.2017.182
|View full text |Cite
|
Sign up to set email alerts
|

Smart Ground Project: A New Approach to Data Accessibility and Collection for Raw Materials and Secondary Raw Materials in Europe

Abstract: Steady Raw Materials (RM) supply is essential for the EU economy and increasingly under pressure to sustain the businesses and industries demand. The supply of RM is not only a matter of availability of primary but also of secondary raw materials (SRM). In fact a great amount of waste can be regained as practical and valuable SRM by enhancing the recovery processes from industrial, mining and municipal landfill sites, especially if we consider that Europe is highly dependent on the imports of several RM. Never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…A key study identified was presented by Panagiotopoulou et al [21], who describe several cases of material recovery from mine waste within the EU and defined the most crucial steps from the idea towards realisation. Other publications used for the literature review were different key reports from the topic [7,14,[22][23][24][25][26], as well as CRIRSCO [27], JORC [28], PERC [29] and UNECE [30] classification codes for reporting the exploration results, mineral resources and reserves and the references contained in the aforementioned documents. The parameters identified included those related to basic site and commodity information, historical framework, data collection methodology, extractability and accessibility of the secondary resources, the policy and legislative environment, as well as the relevant chemical and physical properties.…”
Section: Defining Key Mine Waste Valorisation Data Parametersmentioning
confidence: 99%
“…A key study identified was presented by Panagiotopoulou et al [21], who describe several cases of material recovery from mine waste within the EU and defined the most crucial steps from the idea towards realisation. Other publications used for the literature review were different key reports from the topic [7,14,[22][23][24][25][26], as well as CRIRSCO [27], JORC [28], PERC [29] and UNECE [30] classification codes for reporting the exploration results, mineral resources and reserves and the references contained in the aforementioned documents. The parameters identified included those related to basic site and commodity information, historical framework, data collection methodology, extractability and accessibility of the secondary resources, the policy and legislative environment, as well as the relevant chemical and physical properties.…”
Section: Defining Key Mine Waste Valorisation Data Parametersmentioning
confidence: 99%
“…Territorial environmental agencies from Northern Europe recommend [72] the reuse of recycled products and SRM coming from waste treatment, whenever possible, instead of using natural (non-renewable) resources. In general, sustainable land and resources management is based on the overall organization of materials flows and on the optimization of the recycling activities, including the evaluation of the more suitable and marketable recycled products obtained from EW treatment and recycling activities [73].…”
Section: Extractive Waste Management and Recoverymentioning
confidence: 99%
“…It is often necessary to conduct an Environmental Impact Assessment (EIA), which requires integration of knowledge about the project as it is being designed, the natural and social environments in which the project is situated, and community and stakeholder concerns. Although it is evident that mining activity caused, and in some cases still causes, huge environmental and health impacts [25,26], recent research is changing the perspectives, considering EW facilities as potential new ore bodies to investigate and exploit for RM/CRM recovery [3,[27][28][29]. Old EW facilities often present a significant content of non-exploited minerals: modern processing technologies make possible the exploitation of minerals not mined in the past (e.g., sphalerite vs calamine) and potentially CRM which are often associated with minerals exploited for RM supply [12].…”
Section: Focus On Environmental Impacts and Potential Waste Recovery Associated With Extractive Waste Facilitiesmentioning
confidence: 99%